Math, asked by sohamhanse29, 1 year ago

If tan^3 theta -4√3.tan theta +3=0, then: tan theta =?

Answers

Answered by vamsisudha76
1

Step-by-step explanation:

Tan theta =. a/b

height/base= a/ b

therefore, height= a

base= b

by Pythagoras theorem

hypotenuse square = sum of square of other sides

let hypotenuse be " c"

c square = a square+ b square

therefore, c=the whole square root of a square +b square

sec theta = hypotenuse/base

= the whole square root of a square +b square/ b

hope it helps you mate

Similar questions